Assessment of the Effectiveness of Industrial Gas Purification with Diethanolamine (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The presented work is devoted to the efficiency of industrial purification of DEA from sulfur compounds in gas. To evaluate the efficiency of DEA purification in laboratory conditions, studies were carried out that showed the presence of foaming on samples taken before entering activated carbon and at the exit after 60 days of carbon adsorption purification. To compare the results obtained, a foaming study was also carried out on fresh DEA. The content of high-boiling resinous substances in the composition of DEA was studied by chromatographic and photocolorometric methods of analysis.